The boletes of China : Tylopilus s.l. - Li, Yan-Chun; Yang, Zhu L. (Singapore : Springer ; Beijing : Science Press, 2021)
This book introduces the Chinese boletes, including the history, ecological and economic values, as well as the geographical distribution patterns with a highlight on the Tylopilus species. Species in Tylopilus s.l. are not only of important ecological values but also of scientific interests. They are very diverse in morphology, complex in structure and wide in ecological niches. China is one of the diverse hotspots of boletes, and many boletes were traditionally treated as members of Tylopilus based on hymenophore or spore-print colour. The studies revealed that the traditionally defined Tylopilus is polyphyletic. This book aims to elucidate the phylogenetic relationships among the genera treated in Tylopilus s.l. previously; to delimit and recognize the taxa, and finally to reveal the diversity of the genera and species of Tylopilus s.l. in China. The book is intended to be a reference for biologists who conduct investigations of biological resources and biodiversity; university and college teachers and students carrying out studies in related fields; mycologists and amateur mycologists, or people who interested in mushrooms taxonomy and systematics; and workers in the development of non-timber forest products. .
Chapter 1. Introduction - The Boletes of China -- Chapter 2. Materials and Methods -- Chapter 3. Morphology and structures in Tylopilus s.l -- Chapter 4. Phylogenetic results and systematic treatments of Tylopilus s.l -- Chapter 5. Taxonomic Part -- Chapter 6. Abtylopilus -- Chapter 7. Anthracoporus -- Chapter 8. Austroboletus -- Chapter 9. Chiua -- Chapter 10. Fistulinella -- Chapter 11. Harrya -- Chapter 12. Hymenoboletus -- Chapter 13.Indoporus -- Chapter 14. Leccinum -- Chapter 15. Mucilopilus -- Chapter 16. Porphyrellus -- Chapter 17. Pseudoaustroboletus -- Chapter 18. Retiboletus -- Chapter 19. Royoungia -- Chapter 20. Sutorius -- Chapter 21. Tylocinum -- Chapter 22. Tylopilus -- Chapter 23. Veloporphyrellus -- Chapter 24. Zangia -- Chapter 25. Summary and Conclusion. .
Includes bibliographical references and index.
Online resource; title from PDF title page (SpringerLink, viewed February 14, 2022).
Keywords: Boletales -- China; Bolétales -- Chine; Boletales; China; Electronic books; Electronic books